Anti-reflective film and image display device
By using a primer layer with high content of tin oxide in the antireflective film, the problem of peeling between layers in an existing antireflective film in an acidic environment is solved, and the effect of excellent acid resistance is achieved.
Patent Information
- Application Number
- CN202380067905.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-11
- Filing Date
- 2023-09-13
- Publication Date
- 2025-05-02
AI Technical Summary
The conventional anti-reflective film is prone to interlayer peeling when it comes into contact with the acid, and it is difficult to apply to applications requiring acid resistance.
A primer layer with indium tin oxide as the main component is used, with an amount of tin oxide of 15% by weight or more. Combined with a transparent film base material, a hard coating layer and an anti-reflective layer, an anti-reflective film with excellent acid resistance is formed.
The durability of the anti-reflective film in an acidic environment is achieved, the adhesion between the hard coating and the anti-reflective layer is ensured, and the risk of interlayer peeling is reduced.
Smart Images

Figure CN119923581A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an antireflection film and an image display device. Background Art
[0002] Antireflection films are placed on the viewing side of image display devices such as liquid crystal displays and organic EL displays to prevent image quality degradation caused by reflection of outdoor light and to improve contrast. These films comprise an antireflection layer formed from a laminate of multiple thin films with different refractive indices on a transparent film substrate.
[0003] For example, Patent Document 1 discloses an antireflection film in which a primer layer containing indium tin oxide (ITO) is provided on a hard coat layer, and an antireflection layer composed of a plurality of thin films is formed thereon.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2005-266665 Summary of the Invention
[0007] Problems to be solved by the invention
[0008] According to the research of the present inventors, it is clear that when an anti-reflection film having a conventional ITO film as a primer layer is brought into contact with an acid such as sulfuric acid, interlayer delamination (e.g., interlayer delamination between the anti-reflection layer and the hard coat layer) is likely to occur. Therefore, an anti-reflection film having a conventional ITO film as a primer layer may be difficult to apply to applications requiring acid resistance (the property of withstanding corrosion caused by acid). It should be noted that applications requiring acid resistance include automotive applications (on-board applications) using sulfuric acid in battery fluid.
[0009] In view of the above circumstances, an object of the present invention is to provide an antireflection film having excellent acid resistance and an image display device using the antireflection film.
[0010] Solutions for solving problems
[0011] <Aspects of the present invention>
[0012] The present invention includes the following aspects.
[0013] [1] An antireflection film comprising, in order, a transparent film substrate, a hard coat layer, a primer layer, and an antireflection layer, wherein the antireflection layer is a laminate of a plurality of thin films having different refractive indices, and the primer layer is a thin film containing indium tin oxide as a main component, wherein the amount of tin oxide relative to the total amount of indium oxide and tin oxide is 15% by weight or more.
[0014] [2] The antireflection film according to [1], wherein the amount of tin oxide in the primer layer is 60% by weight or less relative to the total amount of indium oxide and tin oxide.
[0015] [3] The antireflection film according to [1] or [2], wherein the primer layer has a thickness of 0.5 nm to 20 nm.
[0016] [4] The antireflection film according to any one of [1] to [3], further comprising an antifouling layer, wherein the antifouling layer is disposed on the side of the antireflection layer opposite to the primer layer side.
[0017] [5] The antireflection film according to any one of [1] to [4], wherein the hard coat layer contains particles having a number average primary particle size of less than 1.0 μm.
[0018] [6] The antireflection film according to any one of [1] to [5], further comprising an adhesive layer, wherein the adhesive layer is disposed on the side of the transparent film substrate opposite to the hard coat layer.
[0019] [7] An image display device comprising an image display panel and the antireflection film according to any one of [1] to [6] arranged on a visual confirmation side of the image display panel.
[0020] Effects of the Invention
[0021] According to the present invention, an antireflection film having excellent acid resistance and an image display device using the antireflection film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a cross-sectional view showing an example of the antireflection film of the present invention.
[0023] Figure 2 This is a cross-sectional view showing another example of the antireflection film of the present invention.
[0024] Figure 3 It is a cross-sectional view showing an example of the image display device of the present invention. DETAILED DESCRIPTION
[0025] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited thereto. In addition, all academic documents and patent documents described in this specification are incorporated herein by reference.
[0026] First, the terms used in this specification are explained. "Refractive index" refers to the refractive index of light with a wavelength of 550nm in an atmosphere at a temperature of 23°C. The "main surface" of a layered object (more specifically, a transparent film substrate, a hard coat layer, a primer layer, an antireflection layer, an antifouling layer, an adhesive layer, etc.) refers to the surface of the layered object that is perpendicular to the thickness direction. Unless otherwise specified, the thickness (film thickness) of each layer constituting the antireflection film is the following value: 10 measurement locations are randomly selected from the image of the cross section obtained by cutting the layer in the thickness direction, and the thickness of the selected 10 measurement locations is measured to obtain the arithmetic mean of the 10 measurement values.
[0027] Unless otherwise specified, the "main component" of a film (layer) refers to the component that is contained in the largest amount by weight in the film. "Solid content" refers to the non-volatile components in the composition, such as components other than the solvent.
[0028] Unless otherwise specified, the number average primary particle size of the particles is the following value: the number average of the projected area equivalent diameters (Heywood diameter: the diameter of a circle having the same area as the projected area of the primary particles) of 100 primary particles measured using a scanning electron microscope and image processing software (e.g., "ImageJ" manufactured by the National Institutes of Health).
[0029] Hereinafter, "system" may be added after a compound name to collectively refer to the compound and its derivatives. Furthermore, when "system" is added after a compound name to indicate the name of a polymer, unless otherwise specified, it means that the repeating units of the polymer are derived from the compound or its derivatives. Unless otherwise specified, the components and functional groups exemplified in this specification may be used alone or in combination of two or more.
[0030] In the drawings referred to in the following description, the various components are schematically shown on the main body for ease of understanding. The size, number, shape, etc. of the components shown in the drawings may differ from the actual ones for the convenience of drawing. In addition, for ease of explanation, in the drawings described later, components identical to those in the previously described drawings are denoted by the same reference numerals, and their description may be omitted.
[0031] <First embodiment: Antireflection film>
[0032] The antireflection film of the first embodiment of the present invention is an antireflection film (laminate) comprising, in this order, a transparent film substrate, a hard coat layer, a primer layer, and an antireflection layer. The antireflection layer is a laminate of multiple thin films having different refractive indices. The primer layer is a thin film primarily composed of indium tin oxide, with the amount of tin oxide being 15% by weight or greater relative to the total amount of indium oxide and tin oxide.
[0033] Hereinafter, the amount of tin oxide in the primer layer relative to the total amount of indium oxide and tin oxide (100 wt %) (unit: wt %) may be simply referred to as "the amount of tin oxide in the primer layer" or "the amount of tin oxide."
[0034] The antireflection film of the first embodiment has the above-mentioned configuration and therefore has excellent acid resistance. The reason for this is presumably as follows.
[0035] The anti-reflection film of the first embodiment includes a thin film primarily composed of indium tin oxide as a primer layer for improving adhesion between the hard coat layer and the anti-reflection layer. Furthermore, the amount of tin oxide in the primer layer of the anti-reflection film of the first embodiment is 15% by weight or greater. Therefore, the primer layer of the anti-reflection film of the first embodiment is less susceptible to acid corrosion. Therefore, even when exposed to acid, the anti-reflection film of the first embodiment maintains adhesion between the hard coat layer and the anti-reflection layer, resulting in excellent acid resistance.
[0036] Furthermore, the antireflection film of the first embodiment has the above-described configuration, and therefore can ensure interlayer adhesion when irradiated with ultraviolet rays. Hereinafter, the property of ensuring interlayer adhesion when irradiated with ultraviolet rays may be referred to as "weather resistance."
[0037] In the first embodiment, in order to obtain an antireflection film with better acid resistance, the amount of tin oxide in the primer layer is preferably 18 weight % or more, more preferably 20 weight % or more, further preferably 22 weight % or more, and even more preferably 24 weight % or more, and can be 25 weight % or more, 30 weight % or more, 35 weight % or more, or 40 weight % or more.
[0038] In the first embodiment, in order to obtain an antireflection film with excellent transparency, the amount of tin oxide in the primer layer is preferably 60 wt % or less, more preferably 55 wt % or less, further preferably 50 wt % or less, and may be 45 wt % or less.
[0039] Hereinafter, the configuration of the antireflection film according to the first embodiment will be described with reference to the drawings. Figure 1 This is a cross-sectional view showing an example of the antireflection film according to the first embodiment. Figure 1 The antireflection film 10 shown includes, in this order, a transparent film substrate 11, a hard coat layer 12, a primer layer 13, and an antireflection layer 14. The primer layer 13 is in contact with both the hard coat layer 12 and the antireflection layer 14. The primer layer 13 is a thin film mainly composed of indium tin oxide, with the amount of tin oxide being 15% by weight or greater relative to the total amount of indium oxide and tin oxide.
[0040] The antireflection film 10 further includes an antifouling layer 19 disposed on the side of the antireflection layer 14 opposite to the primer layer 13. Specifically, the antireflection film 10 includes the transparent film substrate 11, the hard coat layer 12, the primer layer 13, the antireflection layer 14, and the antifouling layer 19 in this order.
[0041] Anti-reflection layer 14 has high refractive index layer 15, low refractive index layer 16, high refractive index layer 17 and low refractive index layer 18 these four layers from primer layer 13 sides successively.Details about high refractive index layer and low refractive index layer are described in the back.It should be noted that the anti-reflection layer of anti-reflection film is not limited to four layers such as anti-reflection layer 14 and is also possible to be two-layer composition, three-layer composition, five-layer composition or six-layer or more stacked composition.The anti-reflection layer of anti-reflection film is preferably the alternating laminated body of the high refractive index layer more than two layers and the low refractive index layer more than two layers.In order to reduce the reflection at air interface, the preferred outermost layer (the layer farthest from hard coat 12) of the anti-reflection layer of anti-reflection film is a low refractive index layer.
[0042] The antireflection film of the first embodiment may be Figure 1 The anti-reflection film 10 shown is composed of different layers. Figure 2 As shown, the antireflection film of the first embodiment may be an antireflection film 20 further including an adhesive layer 21 disposed on the side of the transparent film substrate 11 opposite to the hard coat layer 12 side.
[0043] The adhesive constituting the adhesive layer 21 is not particularly limited. For example, a transparent adhesive based on a polymer such as an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyvinyl ether, a vinyl acetate / vinyl chloride copolymer, a modified polyolefin, an epoxy resin, a fluororesin, a natural rubber, or a synthetic rubber can be appropriately selected and used. The thickness of the adhesive layer 21 is not particularly limited; however, from the perspective of achieving both thinness and adhesiveness, it is preferably 5 μm to 100 μm.
[0044] A release liner (not shown) may be bonded to the main surface of the adhesive layer 21 on the side opposite to the transparent film substrate 11. The release liner is used, for example, until the anti-reflection film 20 is attached to the image display panel 101 (see FIG. Figure 3 ) until the bonding, the surface of the adhesive layer 21 is protected. As the constituent material of the release liner, a plastic film formed of acrylic acid, polyolefin, cyclic polyolefin, polyester, etc. is preferably used. The thickness of the release liner is, for example, not less than 5 μm and not more than 200 μm. It is preferred to subject the surface of the release liner to a release treatment. As the material of the release agent used for the release treatment, silicone-based materials, fluorine-based materials, long-chain alkyl-based materials, fatty acid amide-based materials, etc. can be listed.
[0045] As mentioned above, the structure of the antireflection film of the first embodiment has been described with reference to the drawings, but the antireflection film of the present invention is not limited to the above structure.
[0046] For example, the antireflection film of the present invention may be an antireflection film without an antifouling layer. In addition, the antireflection film of the present invention may be provided with an optical functional layer different from the layers (transparent film substrate, hard coat layer, primer layer, antireflection layer and antifouling layer) included in the above-mentioned constitution.
[0047] Next, the elements of the antireflection film according to the first embodiment will be described.
[0048] [Transparent film substrate]
[0049] The transparent film substrate is, for example, a flexible transparent resin film. As the material constituting the transparent film substrate, for example, polyester resin, polyolefin resin, polystyrene resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyamide resin, polyimide resin, cellulose resin, norbornene resin, polyarylate resin, and polyvinyl alcohol resin can be cited. As the polyester resin, for example, polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate can be cited. As the polyolefin resin, for example, polyethylene, polypropylene, and cycloolefin polymer (COP) can be cited. As the cellulose resin, for example, triacetyl cellulose (TAC) can be cited. These materials can be used alone or in combination of two or more. As the material of the transparent film substrate, from the viewpoint of transparency and strength, it is preferably one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, more preferably one selected from the group consisting of PET, COP, and TAC, and further preferably TAC. That is, the transparent film substrate is preferably a film selected from the group consisting of polyester resin film, polyolefin resin film, and cellulose resin film, more preferably a film selected from the group consisting of PET film, COP film, and TAC film, and even more preferably TAC film.
[0050] From the viewpoint of strength, the thickness of the transparent film substrate is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. From the viewpoint of handleability, the thickness of the transparent film substrate is preferably 300 μm or less, and more preferably 200 μm or less.
[0051] One or both main surfaces of the transparent film substrate may be subjected to a surface modification treatment. Examples of surface modification treatments include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.
[0052] From the viewpoint of improving the transparency of the antireflection film, the total light transmittance (JIS K7375-2008) of the transparent film substrate is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more and 100% or less.
[0053] [Hard Coating]
[0054] Hard coat is a layer that improves the mechanical properties such as the hardness and elastic modulus of the anti-reflection film. The hard coat is formed by a cured product of a curable resin composition (composition for forming a hard coat). As the curable resin contained in the curable resin composition, for example, polyester resin, acrylic resin, carbamate resin, carbamate acrylate resin, amide resin, silicone resin, epoxy resin, and melamine resin can be listed. These curable resins can be used alone or in combination of two or more. From the viewpoint of improving the hardness of the hard coat, as the curable resin, it is preferably one or more selected from the group consisting of acrylic resin and carbamate acrylate resin, more preferably carbamate acrylate resin.
[0055] In addition, as a curable resin composition, for example, a UV-curable resin composition and a thermosetting resin composition can be listed. From the viewpoint of improving the productivity of the anti-reflection film, as a curable resin composition, a UV-curable resin composition is preferably a UV-curable resin composition. The UV-curable resin composition contains one or more selected from the group consisting of a UV-curable monomer, a UV-curable oligomer, and a UV-curable polymer. As a specific example of a UV-curable resin composition, a hard coat forming composition described in Japanese Patent Application Laid-Open No. 2016-179686 can be listed.
[0056] In addition, the curable resin composition may contain microparticles. By adding microparticles to the curable resin composition, the hardness, surface roughness, refractive index, and anti-glare properties of the hard coat layer can be adjusted. Examples of microparticles include metal (or semi-metal) oxide particles, glass particles, and organic particles. Examples of materials for metal (or semi-metal) oxide particles include silicon dioxide, aluminum oxide, titanium dioxide, zirconium oxide, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of materials for organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.
[0057] In addition, the curable resin composition may contain particles having a number average primary particle size of less than 1.0 μm (hereinafter sometimes referred to as "nanoparticles") as the above-mentioned microparticles. In other words, the hard coat layer may contain nanoparticles. When the hard coat layer is formed from a cured product of a curable resin composition containing nanoparticles, fine concavo-convex patterns are formed on the surface of the hard coat layer, and there is a tendency for the hard coat layer to have improved adhesion to a layer formed thereon (e.g., a primer layer).
[0058] From the viewpoint of forming fine concavo-convex shapes that contribute to improved adhesion, the number average primary particle size of the nanoparticles is preferably 20 nm to 80 nm, more preferably 25 nm to 70 nm, and even more preferably 30 nm to 60 nm.
[0059] As the material of the nanoparticles, inorganic oxides are preferred. Examples of inorganic oxides include oxides of metals (or semi-metals) such as silicon oxide (silicon dioxide), titanium oxide, aluminum oxide, zirconium oxide, niobium oxide, zinc oxide, tin oxide, cerium oxide, and magnesium oxide. The inorganic oxide can be a composite oxide of multiple (semi-)metals. Among the inorganic oxides exemplified, silicon oxide is preferred due to its high adhesion-enhancing effect. In other words, as nanoparticles, silicon oxide particles (silicon dioxide particles) are preferred. In order to improve adhesion and affinity with resins, functional groups such as acryloyl groups and epoxy groups can be introduced onto the surface of the inorganic oxide particles serving as nanoparticles.
[0060] The amount of the nanoparticle in the hard coning is preferably more than 5 weight parts with respect to curable resin 100 weight parts, can be more than 10 weight parts, more than 20 weight parts or more than 30 weight parts.If the amount of nanoparticle is more than 5 weight parts, then can make and the adhesion of the layer formed on the hard coning further improve.The upper limit of the amount of the nanoparticle in the hard coning is for example, 90 weight parts with respect to curable resin 100 weight parts, is preferably 80 weight parts, can be 70 weight parts.
[0061] From the perspective of increasing the hardness of the hard coat layer, the thickness of the hard coat layer is preferably 1 μm or more, more preferably 2 μm or more. From the perspective of ensuring the flexibility of the antireflection film, the thickness of the hard coat layer is preferably 50 μm or less, more preferably 40 μm or less, further preferably 35 μm or less, and even more preferably 30 μm or less.
[0062] The main surface of the hard coat layer on the side opposite to the transparent film substrate side may be subjected to surface modification. Examples of surface modification treatments include plasma treatment, corona treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment. In order to improve the adhesion between the layer (e.g., primer layer described later) provided on the side opposite to the transparent film substrate side of the hard coat layer and the hard coat layer, the main surface of the hard coat layer on the side opposite to the transparent film substrate side is preferably subjected to plasma treatment.
[0063] [Primer layer]
[0064] The primer layer is a layer for improving the adhesion of the hard coat layer to the anti-reflection layer. In the present embodiment, the primer layer is a film with indium tin oxide (ITO) as the main component. The primer layer includes ITO as the main component, thereby improving the adhesion of the hard coat layer to the anti-reflection layer and the primer layer having excellent transparency. In addition, the primer layer includes ITO as the main component, thereby making the anti-reflection film have appropriate antistatic properties.
[0065] The primer layer may contain oxides other than indium oxide and tin oxide. However, in order to further improve the adhesion between the hard coat layer and the antireflection layer, the ITO content in the primer layer is preferably 90% by weight or more, and more preferably 99% by weight or more, relative to the total weight of the primer layer. Hereinafter, a film containing ITO as a main component may be referred to as an "ITO layer."
[0066] To improve adhesion between the hard coat layer and the antireflection layer and ensure transparency of the primer layer, the primer layer preferably has a thickness of 0.5 nm to 20 nm, more preferably 0.5 nm to 10 nm, and even more preferably 1.0 nm to 10 nm.
[0067] [Anti-reflection layer]
[0068] The antireflection layer is composed of two or more thin films with different refractive indices. Typically, the optical thickness (the product of refractive index and thickness) of the antireflection layer is adjusted so that the phase reversals of incident and reflected light cancel each other out. By using a multilayered stack of two or more thin films with different refractive indices as the antireflection layer, reflectivity can be reduced across a wide wavelength range of visible light.
[0069] Examples of materials constituting the thin film of the antireflection layer include metal (or semimetal) oxides, nitrides, fluorides, etc. The antireflection layer is preferably an alternating stack of high refractive index layers and low refractive index layers.
[0070] The refractive index of the high refractive index layer is, for example, 1.9 or more, preferably 2.0 or more. As the material of the high refractive index layer, titanium oxide, niobium oxide (Nb2O5, etc.), zirconium oxide, tantalum oxide, zinc oxide, indium oxide, antimony-doped tin oxide (ATO), etc. can be listed. Among them, it is preferably one or more selected from the group consisting of titanium oxide and niobium oxide. The refractive index of the low refractive index layer is, for example, 1.6 or less, preferably 1.5 or less. As the material of the low refractive index layer, silicon oxide (SiO2, etc.), titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, lanthanum fluoride, etc. can be listed. Among them, silicon oxide is preferred. It is particularly preferred to alternately stack a niobium oxide thin film as a high refractive index layer and a silicon oxide thin film as a low refractive index layer. In addition to the low refractive index layer and the high refractive index layer, a medium refractive index layer having a refractive index greater than 1.6 and less than 1.9 can also be provided.
[0071] The thickness of high refractive index layer and low refractive index layer is preferably respectively more than 5nm and below 200nm, more preferably more than 10nm and below 150nm.According to refractive index, stacking formation etc., the thickness of each layer is designed in the mode that the reflectivity of visible light tapers down.For example, as the stacking formation of high refractive index layer and low refractive index layer, can list out: from hard coat side by optical thickness 20nm more than and the high refractive index layer below 55nm, optical thickness 25nm more than and the low refractive index layer below 55nm, optical thickness 80nm more than and the high refractive index layer below 270nm and optical thickness 100nm more than and the low refractive index layer below 150nm four layers of formation.
[0072] In the case where the antireflection layer is a four-layer alternating stack formed by alternately stacking a niobium oxide thin film as a high refractive index layer and a silicon oxide thin film as a low refractive index layer, the antireflection layer may include, in order from the hard coat layer side, a niobium oxide thin film having a thickness of 5 nm to 20 nm, a silicon oxide thin film having a thickness of 10 nm to 40 nm, a niobium oxide thin film having a thickness of 65 nm to 120 nm, and a silicon oxide thin film having a thickness of 60 nm to 100 nm.
[0073] In order to obtain an anti-reflection film with excellent bending resistance, the thickness of the anti-reflection layer is preferably 140 nm to 280 nm, more preferably 170 nm to 280 nm, further preferably 180 nm to 260 nm, and even more preferably 190 nm to 250 nm. It should be noted that in this specification, the "thickness of the anti-reflection layer" refers to the sum of the thicknesses of the layers constituting the anti-reflection layer (total thickness).
[0074] [Antifouling layer]
[0075] The anti-reflection film preferably includes an anti-fouling layer on the side of the anti-reflection layer opposite to the primer layer, and more preferably includes the anti-fouling layer as the outermost layer of the anti-reflection film. The anti-fouling layer can reduce the effects of external environmental contamination (such as fingerprints, hand dirt, and dust) and facilitate the removal of contaminants adhering to the surface of the anti-reflection film.
[0076] To prevent the antireflection performance of the antireflection layer from being reduced, the antifouling layer preferably has a small refractive index difference from the outermost layer (e.g., low refractive index layer) of the antireflection layer. The refractive index of the antifouling layer is preferably 1.6 or less, more preferably 1.55 or less.
[0077] As the material of the antifouling layer, a fluorine-containing compound is preferably used. Fluorine-containing compounds have excellent antifouling properties and can contribute to a low refractive index. Among them, from the perspective of excellent hydrophobicity and the ability to exert high antifouling properties, an alkoxysilane compound containing a perfluoropolyether skeleton is preferred. As an alkoxysilane compound containing a perfluoropolyether skeleton, for example, an alkoxysilane compound having a plurality of linear or branched perfluorooxyalkylene units having a carbon number of 1 or more and 4 or less can be cited. As a linear or branched perfluorooxyalkylene unit having a carbon number of 1 or more and 4 or less, for example, a perfluorooxymethylene unit (-CF2O-), a perfluorooxyethylene unit (-CF2CF2O-), a perfluorooxypropylene unit (-CF2CF2CF2O-), a perfluorooxyisopropylene unit (-CF(CF3)CF2O-), etc. can be cited.
[0078] The thickness of the antifouling layer is, for example, from 2 nm to 20 nm. There is a tendency that the thicker the antifouling layer, the better the antifouling properties. The thickness of the antifouling layer is preferably 5 nm or more, more preferably 6 nm or more. On the other hand, from the perspective of improving anti-glare properties, the thickness of the antifouling layer is preferably 15 nm or less.
[0079] [Preferred embodiment of antireflection film]
[0080] In order to obtain an antireflection film having excellent acid resistance while ensuring weather resistance and transparency, the antireflection film of the first embodiment preferably satisfies the following condition 1, more preferably satisfies the following condition 2, and even more preferably satisfies the following condition 3.
[0081] Condition 1: The amount of tin oxide in the primer layer is 15% by weight or more and 60% by weight or less.
[0082] Condition 2: The above-mentioned condition 1 is satisfied and the thickness of the primer layer is 0.5 nm to 20 nm.
[0083] Condition 3: The above-mentioned condition 2 is satisfied, and the hard coat layer contains particles having a number average primary particle size of less than 1.0 μm.
[0084] [Method for producing antireflection film]
[0085] Next, a preferred method for producing the antireflection film of the first embodiment will be described. Hereinafter, the preferred method for producing the antireflection film of the first embodiment may be described as a production method M.
[0086] The manufacturing method M includes, for example, a primer layer forming step and an antireflection layer forming step. The manufacturing method M may include steps (other steps) other than the primer layer forming step and the antireflection layer forming step. Examples of the other steps include a hard coat layer forming step, a hard coat layer surface treatment step, and an antifouling layer forming step, which will be described later.
[0087] Hereinafter, each step included in an example of the manufacturing method M will be described.
[0088] (Hard Coat Formation Step)
[0089] The hard coat layer forming step is a step of forming a hard coat layer on one main surface of a transparent film substrate. For example, a curable resin composition (hard coat layer forming composition) is applied to one main surface of a transparent film substrate, and the solvent is removed and the resin is cured as needed to form the hard coat layer. The hard coat layer forming composition, for example, comprises the aforementioned curable resin and a polymerization initiator (e.g., a photopolymerization initiator), and optionally a solvent capable of dissolving or dispersing these components.
[0090] In addition to the above-mentioned components, the hard coat forming composition may also contain additives such as nanoparticles, particles with a number average primary particle size of 1.0 μm or more, leveling agents, viscosity modifiers (thixotropic agents, thickeners, etc.), antistatic agents, anti-blocking agents, dispersants, dispersion stabilizers, antioxidants, ultraviolet absorbers, defoaming agents, surfactants, lubricants, etc.
[0091] As a coating method for the hard coat forming composition, any appropriate method such as rod coating, roller coating, gravure coating, rod coating, slot orifice coating, curtain coating, injection coating, and notch wheel coating can be adopted. The drying temperature of the coating film after coating can be set to an appropriate temperature according to the composition of the hard coat forming composition, for example, 50°C or more and 150°C or less. When the resin component in the hard coat forming composition is a thermosetting resin, the coating film is cured by heating. When the resin component in the hard coat forming composition is a photocurable resin, the coating film is cured by irradiating active energy rays such as ultraviolet rays. The cumulative light amount of the irradiated light is preferably 100mJ / cm 2 Above and 500mJ / cm 2 the following.
[0092] (Surface treatment process of hard coating)
[0093] In the surface treatment process of the hard coat layer, the main surface of the hard coat layer on the side opposite to the transparent film substrate side is subjected to a surface modification treatment. Examples of surface modification treatments include plasma treatment, corona treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment. When the surface modification treatment is a plasma treatment, argon gas is used as an inert gas, for example. In addition, the discharge power in the plasma treatment is, for example, 50 W or more and 300 W or less. In addition, the pressure conditions in the plasma treatment are, for example, 0.1 Pa or more and 2.5 Pa or less.
[0094] (Primer layer forming step)
[0095] The primer layer forming process is a process for forming (film formation) a primer layer on a hard coat layer. The film forming method of the primer layer is not particularly limited and can be any one of a wet coating method and a dry coating method. From the perspective of being able to form a thin film with uniform film thickness, dry coating methods such as a vacuum evaporation method, a CVD method, and a sputtering method are preferably used. From the viewpoint of improving productivity, as the film forming method of the primer layer, a method for film formation using a roll-to-roll sputtering film forming device (roll-to-roll sputtering method) is preferably used.
[0096] In the roll-to-roll sputtering method, a long film (e.g., a transparent film substrate with a hard coat layer formed thereon) can be continuously formed into films such as a primer layer and an anti-reflection layer while being transported in the longitudinal direction (MD direction). In the sputtering method, film formation is carried out while an inert gas such as argon and, as needed, a reactive gas such as oxygen are introduced into the film forming chamber. In the case of forming an ITO layer as a primer layer, the sputtering method can be used to form the ITO layer using an oxide target or reactive sputtering using a metal (or semi-metal) target.
[0097] As a power source for implementing the sputtering method, for example, a DC power supply, an AC power supply, an RF power supply, and an MFAC power supply (an AC power supply with a frequency band of several kHz to several MHz) can be listed. The discharge power in the sputtering method is, for example, 1 kW or more and 100 kW or less, preferably 1 kW or more and 50 kW or less. The surface temperature of the film-forming roller when implementing the sputtering method is, for example, -25°C or more and 25°C or less, preferably -20°C or more and 0°C or less. The pressure in the film-forming chamber when implementing the sputtering method is preferably 0.01 Pa or more and 10 Pa or less, more preferably 0.05 Pa or more and 5 Pa or less, and even more preferably 0.1 Pa or more and 1 Pa or less.
[0098] (Anti-reflection layer forming step)
[0099] The anti-reflection layer forming process is a process for forming an anti-reflection layer on the primer layer. The film forming method of the anti-reflection layer is not particularly limited and can be any of a wet coating method and a dry coating method. From the perspective of being able to form a thin film with uniform film thickness, dry coating methods such as vacuum evaporation, CVD, and sputtering are preferred. From the perspective of improving productivity, as the film forming method of the anti-reflection layer, a method of forming the film using a roll-to-roll sputtering film forming device (roll-to-roll sputtering method) is preferred. When the sputtering method is implemented in the anti-reflection layer forming process, for example, the film forming conditions can be appropriately set among the conditions described in the above-mentioned (primer layer forming process).
[0100] (Antifouling layer forming step)
[0101] The antifouling layer forming step is a step of forming an antifouling layer on the side of the antireflection layer opposite to the primer layer. In this step, for example, a fluorine-containing compound is used as the material and the antifouling layer is formed by a dry coating method. Examples of dry coating methods include vacuum evaporation, sputtering, and CVD, with vacuum evaporation being preferred.
[0102] <Second Embodiment: Image Display Device>
[0103] Next, an image display device according to a second embodiment of the present invention will be described. The image display device according to the second embodiment includes an image display panel and the antireflection film according to the first embodiment, which is disposed on the visual confirmation side of the image display panel. The following description will omit any overlap with the first embodiment.
[0104] Figure 3 This is a cross-sectional view showing an example of an image display device according to the second embodiment. Figure 3 The image display device 100 shown in the figure includes an image display panel 101 and an anti-reflection film 10. The anti-reflection film 10 is disposed on the visual confirmation side ( Figure 3 In the image display device 100 , the transparent film substrate 11 of the antireflection film 10 and the image display panel 101 are bonded together via the adhesive layer 21 .
[0105] As the image display panel 101 , an image display panel including an image display cell such as a liquid crystal cell or an organic EL cell can be exemplified.
[0106] The image display device of the second embodiment has an antireflection film disposed on the visual confirmation side of the image display panel, thereby reducing reflection of outdoor light and improving visibility. In addition, the image display device of the second embodiment has excellent acid resistance due to the antireflection film of the first embodiment.
[0107] Example
[0108] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.
[0109] <Production of Antireflection Film of Example 1>
[0110] [Hard Coat Formation Step]
[0111] A urethane acrylate-based ultraviolet curable resin composition containing silica particles having a number average primary particle size of 50 nm ("Beamset 577" manufactured by Arakawa Chemical Industries, Ltd.), 0.1 parts by weight of silicone resin particles ("Tospearl 130" manufactured by Momentive Performance Materials Japan, average particle size: 3.0 μm, refractive index: 1.43, true specific gravity: 1.32), 4.0 parts by weight of cross-linked polymethyl methacrylate (PMMA) particles ("Techpolymer SSX-103" manufactured by Sekisui Chemicals, Ltd., average particle size: 3.0 μm, refractive index: 1.50, true specific gravity: 1.20), 2.0 parts by weight of a thixotropic agent ("SUMECTON SAN" manufactured by Kunimine Industries, Ltd., synthetic montmorillonite as an organoclay), 3.0 parts by weight of a photopolymerization initiator (IGM) were mixed with the mixture. Resins Co., Ltd. "Omnirad127"), and 0.15 parts by weight of a silicone leveling agent (Kyoeisha Chemical Co., Ltd. "Polyflow LE303") were mixed and diluted with butyl acetate to obtain a hard coat layer forming composition HC1 having a solid content concentration of 40% by weight. Next, the hard coat layer forming composition HC1 obtained in the above step was applied to one main surface of a TAC film (Fujifilm Corporation "Fujitac TG60UL", thickness: 60 μm) serving as a transparent film substrate to form a coating film. Next, the coating film was dried by heating it at a temperature of 60°C for 60 seconds and then cured by ultraviolet irradiation. During ultraviolet irradiation, a high-pressure mercury lamp was used as a light source, ultraviolet rays with a wavelength of 365 nm were used, and the cumulative light intensity was set to 300 mJ / cm 2 Thus, a hard coat layer having a thickness of 6 μm was formed on the TAC film.
[0112] [Surface treatment process of hard coating]
[0113] Next, the TAC film with the hard coating formed thereon was transported in a roll-to-roll plasma treatment apparatus under a vacuum atmosphere of 1.0 Pa while the surface of the hard coating was subjected to plasma treatment. During the plasma treatment, argon was used as an inert gas, and the discharge power was set to 100 W. This produced a laminate comprising a TAC film and a plasma-treated hard coating (hereinafter sometimes referred to as "optical film F1").
[0114] [Primer layer forming step]
[0115] Next, the optical film F1 was introduced into a roll-to-roll sputtering film forming apparatus, and the pressure in the film forming chamber was reduced to 1×10 - 4 Pa. Subsequently, while conveying the optical film F1, argon and oxygen were introduced at a volume ratio of 100:13, the surface temperature of the film-forming roller was set to -8°C, and a 1.5nm thick ITO layer (primer layer) was formed on the hard coat layer by sputtering. For the formation of the primer layer, an ITO target containing indium oxide and tin oxide at a weight ratio of 85:15 was used as the target material. Furthermore, when forming the film by sputtering, the power supply was an MFAC power supply, the discharge power was set to 4.5kW, and the pressure in the film-forming chamber was set to 0.2Pa.
[0116] [Anti-reflection layer forming step]
[0117] After forming the primer layer, a roll-to-roll sputtering system was used to deposit the primed optical film F1. The following layers were deposited on the primer layer in the following order: a 12nm-thick Nb2O5 layer (refractive index: 2.33), a 27nm-thick SiO2 layer (refractive index: 1.46), a 108nm-thick Nb2O5 layer, and a 86nm-thick SiO2 layer. This resulted in a four-layer antireflection layer (first, second, third, and fourth layers) formed on the primer layer. During the deposition of each of the first, second, third, and fourth layers, the deposition roll surface temperature was set at -8°C, the power supply was an MFAC power source, and the pressure in the deposition chamber was set at 0.7 Pa. Furthermore, during the deposition of the first layer, a Nb target was used, argon and oxygen were introduced at a volume ratio of 100:5, and the discharge power was set at 13.0 kW. For the second layer, a Si target was used, argon and oxygen were introduced at a volume ratio of 100:33, and the discharge power was set to 25.5 kW. For the third layer, a Nb target was used, argon and oxygen were introduced at a volume ratio of 100:13, and the discharge power was set to 27.5 kW. For the fourth layer, a Si target was used, argon and oxygen were introduced at a volume ratio of 100:30, and the discharge power was set to 20.5 kW.
[0118] [Antifouling layer forming step]
[0119] An 8 nm thick antifouling layer was formed on the antireflection layer by vacuum deposition using a dried and solidified coating agent ("SHIN-ETSU SUBELYN KY1903-1" manufactured by Shin-Etsu Chemical Co., Ltd.; active ingredient: an alkoxysilane compound containing a perfluoropolyether skeleton) as a vapor deposition source. The vapor deposition source was heated to 260°C. This yielded an antireflection film (the antireflection film of Example 1) comprising a TAC film, a hard coat layer, a primer layer, an antireflection layer, and an antifouling layer in this order.
[0120] <Production of Antireflection Film of Example 2>
[0121] An antireflection film of Example 2 was obtained by the same production method as in Example 1, except that an ITO target containing indium oxide and tin oxide at a weight ratio of 80:20 was used as a target material in the primer layer forming step.
[0122] <Production of Antireflection Film of Example 3>
[0123] An antireflection film of Example 3 was obtained by the same production method as in Example 1, except that an ITO target containing indium oxide and tin oxide at a weight ratio of 75:25 was used as a target material in the primer layer forming step.
[0124] <Production of Antireflection Film of Example 4>
[0125] An antireflection film of Example 4 was obtained by the same production method as in Example 1, except that an ITO target containing indium oxide and tin oxide at a weight ratio of 70:30 was used as a target material in the primer layer forming step.
[0126] <Production of Antireflection Film of Example 5>
[0127] An antireflection film of Example 5 was obtained by the same production method as in Example 1, except that an ITO target containing indium oxide and tin oxide at a weight ratio of 60:40 was used as a target material in the primer layer forming step.
[0128] <Preparation of Antireflection Film of Comparative Example 1>
[0129] An antireflection film of Comparative Example 1 was obtained by the same production method as in Example 1, except that an ITO target containing indium oxide and tin oxide at a weight ratio of 90:10 was used as a target material in the primer layer forming step.
[0130] <Preparation of Antireflection Film of Reference Example 1>
[0131] An antireflection film of Reference Example 1 was obtained by the same production method as in Example 1 except that the primer layer forming step was changed to the following procedure.
[0132] [Primer layer forming step of reference example 1]
[0133] The optical film F1 was introduced into a roll-to-roll sputtering film forming apparatus, and the pressure in the film forming chamber was reduced to 1×10 -4 Pa. Subsequently, while conveying the optical film F1, argon and oxygen were introduced at a volume ratio of 100:9, and the surface temperature of the film-forming roller was set to -8°C. A 3.0nm thick SiOx layer (x < 2) was formed on the hard coat layer by sputtering. A Si target was used as the target material for forming the primer layer (SiOx layer). Furthermore, during sputtering, the power source was an MFAC power supply, the discharge power was set to 4.5kW, and the pressure in the film-forming chamber was set to 0.7Pa.
[0134] <Preparation of Antireflection Film of Reference Example 2>
[0135] An antireflection film of Reference Example 2 was obtained by the same production method as in Example 1 except that the primer layer forming step was changed to the following steps.
[0136] [Primer layer forming step of reference example 2]
[0137] The optical film F1 was introduced into a roll-to-roll sputtering film forming apparatus, and the pressure in the film forming chamber was reduced to 1×10 -4 Pa. Subsequently, while conveying the optical film F1, argon and oxygen were introduced at a volume ratio of 100:10, and the surface temperature of the film-forming roller was set to -8°C. A TiOx layer (x < 2) with a thickness of 1.5 nm was formed on the hard coat layer by sputtering. A Ti target was used as the target material for forming the primer layer (TiOx layer). Furthermore, during sputtering, the power source was an MFAC power supply, the discharge power was set to 4.5 kW, and the pressure in the film-forming chamber was set to 0.7 Pa.
[0138] <Measurement and evaluation methods>
[0139] [Method for measuring the amount of tin oxide]
[0140] The amount of tin oxide in the primer layer of the antireflection film to be measured (specifically, any one of the antireflection films of Examples 1 to 5 and Comparative Example 1) was measured according to the following procedure. First, a primer layer with a thickness of 1.5 nm was formed on the hard coat layer of the optical film F1 under the same conditions as those for the primer layer of the antireflection film to be measured. Next, the elemental composition of the obtained primer layer was measured using a scanning fluorescent X-ray analyzer ("ZSX PrimusII" manufactured by Rigaku Corporation). Then, the amount of tin oxide relative to the sum of indium oxide and tin oxide was calculated (unit: weight %).
[0141] [Evaluation method of acid resistance]
[0142] One drop of sulfuric acid aqueous solution ("37% (1+3)-sulfuric acid" manufactured by Kishida Chemical Co., Ltd., sulfuric acid concentration: 37% by weight, water concentration: 63% by weight) was added to the antifouling layer surface of the antireflection film to be evaluated (specifically, any of the antireflection films of Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2) using a dropper. The solution was then allowed to stand for 22 hours in an atmosphere at a temperature of 23°C and a relative humidity of 50%. The antifouling layer surface was then washed with water, and the presence of interlayer delamination in the antireflection film was visually inspected. A rating of A (excellent acid resistance) was assigned for the absence of interlayer delamination. On the other hand, a rating of B (poor acid resistance) was assigned for the presence of interlayer delamination.
[0143] [Weather resistance evaluation method]
[0144] First, a 5 mm thick glass plate was bonded to the TAC film-side main surface of the antireflection film to be evaluated (specifically, any of the antireflection films of Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2) via an adhesive to prepare an evaluation sample. Next, the evaluation sample was placed in a weathering tester ("Eye Super SUV-W161" manufactured by Iwasaki Electric Co., Ltd.) and irradiated with ultraviolet light from the antifouling layer side under the following conditions.
[0145] (Ultraviolet irradiation conditions)
[0146] Black Panel Temperature (BPT): 85°C.
[0147] Relative humidity: 45%.
[0148] UV intensity: 150mW / cm 2 .
[0149] Irradiation time: 32.5 hours.
[0150] Next, a cross-cut peeling test was conducted using 100 squares formed on the antifouling layer side of the antireflection film after UV irradiation, according to JIS K5400 (cross-cut test method). The number of peeled squares was counted, and weather resistance was evaluated according to the following criteria. "Peeling" refers to peeling of at least one-quarter of the area of a single square.
[0151] A: The number of peeled squares is 9 or less.
[0152] B: The number of peeled squares is 10 or more.
[0153] A case where the judgment result was A was evaluated as “excellent weather resistance.” On the other hand, a case where the judgment result was B was evaluated as “poor weather resistance.”
[0154] Results
[0155] Table 1 shows the types of oxides constituting the primer layer, the amount of tin oxide, the acid resistance evaluation results, and the weather resistance evaluation results for Examples 1 to 5, Comparative Example 1, and Reference Examples 1 and 2. In Table 1, “-” indicates that no measurement was performed.
[0156] [Table 1]
[0157]
[0158] As shown in Table 1, the amount of tin oxide in the primer layer was 15% by weight or more in Examples 1 to 5. The evaluation results of acid resistance in Examples 1 to 5 were A. Therefore, the antireflection films of Examples 1 to 5 were excellent in acid resistance.
[0159] As shown in Table 1, the amount of tin oxide in the primer layer in Comparative Example 1 was less than 15% by weight. The evaluation result of acid resistance in Comparative Example 1 was B. Therefore, the antireflection film of Comparative Example 1 was not good in acid resistance.
[0160] In addition, regarding weather resistance, all the samples except Reference Example 2 in which a TiOx layer was provided as a primer layer were rated A (excellent weather resistance).
[0161] The above results show that the present invention can provide an antireflection film having excellent acid resistance.
[0162] Description of Reference Numerals
[0163] 10, 20: antireflection film; 11: transparent film substrate; 12: hard coating layer; 13: primer layer; 14: antireflection layer; 19: antifouling layer; 21: adhesive layer; 100: image display device; 101: image display panel.
Claims
1. An antireflection film, which comprises a transparent film substrate, a hard coating layer, a primer layer and an antireflection layer in this order, The anti-reflection layer is a laminate of multiple thin films with different refractive indices. The primer layer is a thin film mainly composed of indium tin oxide, and the amount of tin oxide is 15% by weight or more relative to the total amount of indium oxide and tin oxide.
2. The antireflection film according to claim 1, wherein In the primer layer, the amount of tin oxide relative to the total amount of indium oxide and tin oxide is 60% by weight or less.
3. The antireflection film according to claim 1, wherein The primer layer has a thickness of 0.5 nm or more and 20 nm or less.
4. The antireflection film according to claim 1, wherein The antireflection film further includes an antifouling layer disposed on a side of the antireflection layer opposite to the primer layer side.
5. The antireflection film according to claim 1, wherein The hard coating layer includes particles having a number average primary particle size of less than 1.0 μm.
6. The antireflection film according to claim 1, wherein The antireflection film further includes a pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is disposed on the side of the transparent film substrate opposite to the hard coat layer side. 7 . An image display device comprising an image display panel and the antireflection film according to claim 1 disposed on a visual confirmation side of the image display panel.